Resolving species delimitation within the genus Bunopus Blanford, 1874 (Squamata: Gekkonidae) in Iran using DNA barcoding approach - Khosravani, Azar; Rastegar-Pouyani, Eskandar; Rastegar-Pouyani, Nasrullah; Oraie, Hamzeh; Papenfuss, Theodore J. (Zootaxa, 2017)
Mitochondrial COI sequences were used to investigate species delimitation within the genus Bunopus in Iran. A dataset with a final sequence length of 633 nucleotides including 100 specimens from 31 geographically distant localities across Iran were generated. The result demonstrated that two major clades with strong support can be identified within the genus Bunopus in Iran. Clade A includes Bunopus crassicaudus and two new entities, eastern populations (subclade A2,1) and Shahdad populations (subclade A2,2). The second clade comprises western and southwestern populations (subclade B1,1), Arabian populations (subclade B1,2) and south and southeast populations in Iran, to which Bunopus tuberculatus (subclade B2) is assigned. In addition to Bunopus crassicaudus and B. tuberculatus, three new candidate species in Iran can easily be identified based on the DNA barcoding approach.